2008
DOI: 10.1007/s00383-008-2141-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of acetylcholinesterase activity in rectal suction biopsy for diagnosis of intestinal dysganglionoses: 17-year experience of a single center

Abstract: Although the utility of the acetylcholinesterase (AChE) histochemistry on rectal suction biopsy in diagnosing Hirschsprung's disease (HD) has been documented, few reports address a great number of biopsies and patients. Our aim is to present a 17-year experience on the method of rectal suction biopsy and AChE histochemical staining for diagnosis of intestinal dysganglionoses. Between August 1989 and July 2006, 297 children suspected of having HD were submitted to rectal suction biopsies that were evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
0
15
0
10
Order By: Relevance
“…In a recent study, children suspected of having HD were submitted to rectal suction and there were inadequate procedures leading to repeated biopsies in 6% of patients. 21 Nerve cell bodies in both submucosa and myenteric ganglia of guinea pig 22,23 and in the human gastrointestinal tract are immunopositive for calretinin, a calcium-binding protein. 24 Recently, it has been suggested that calretinin might be more accurate than acetylcholinesterase in detecting aganglionosis 18 in a small series of rectal biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, children suspected of having HD were submitted to rectal suction and there were inadequate procedures leading to repeated biopsies in 6% of patients. 21 Nerve cell bodies in both submucosa and myenteric ganglia of guinea pig 22,23 and in the human gastrointestinal tract are immunopositive for calretinin, a calcium-binding protein. 24 Recently, it has been suggested that calretinin might be more accurate than acetylcholinesterase in detecting aganglionosis 18 in a small series of rectal biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnoses were confirmed by rectal suction biopsy to reveal the presence of cholinergic acetylcholinesterasepositive nerve fibers [12]. The patients having a too long aganglionic segment or total colonic aganglionosis were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Acetylcholinesterase histochemical staining is the most commonly applied ancillary method and was reported to have excellent sensitivity and specificity for the diagnosis of HD [2]. However, this method requires frozen specimens, and its interpretation can be difficult for inexperienced pathologists [3].…”
mentioning
confidence: 99%